Screening for ELANE, HAX1 and GFI1 gene mutations in children with neutropenia and clinical characterization of two novel mutations in ELANE gene - Patcharee Komvilaisak; Najwa Yudhasompop; Kittima Kanchanakamhaeng; Suradej Hongeng; Samart Pakakasama; Usanarat Anurathapan; Pongpak Pongphitcha; Duantida Songdej; Werasak Sasanakul; Nongnuch Sirachainan (BMC, 2023)
Abstract Background Congenital neutropenia is a rare disease. Recurrent infections since young age are the presentation. The most common mutation causing severe congenital neutropenia (SCN) and cyclic neutropenia (CyN) is the ELANE gene. The objectives of this study were to screen the three common genetic mutations of ELANE, HAX1 and GFI1 in children with chronic neutropenia and to describe the clinical characteristics of children who had the mutations. Methods Infants having ANC < 1,000/cu mm or children aged > 1 year having ANC < 1,500/cu mm at least 3 times in 3 months were enrolled in the study. Patients who had acquired neutropenia due to infection, immune deficiency, or drugs were excluded. The ELANE gene was first studied; and if mutations were not identified, the HAX1 and GFI1 genes were further examined. Results A total of 60 patients were enrolled in the study. The median (range) age, ratio of female to male, ANC, and last follow-up age were 9.2 (0.5-45.2) months, 1:1.2, 248 (0-1,101) /cu mm, and 19.9 (3.5-202.3) months, respectively. Infections were noted in 67.3% of all patients. ELANE gene mutation was found in only four patients (6.7%), and the rest (56 patients) showed no mutations in the HAX1 and GFI1 genes. In patients without mutations, 66.0% had normal ANC during the follow-up, with a median (range) age for normal ANC of 19.8 (4.0-60.0) months. Two novel mutations p. Ala79del (c.234_236del) and p. Val197GlufsTer18 (c.589_590insAGGCCGGC) were identified, and they respectively cause SCN and CyN. Patients with the two novel mutations presented with several episodes of infection, including pneumonia, sepsis, abscess, otitis media, and gum infection. Conclusion The genetic screening for ELANE, HAX1, and GFI1 gene mutations in 60 patients with chronic neutropenia could identify four patients (6.7%) with ELANE gene mutation and two novel mutations, p. Ala79del in exon 3 and p. Val197GlufsTer18 in exon 4 causing SCN; and CyN, respectively.